Observation of a singular Weyl point surrounded by charged nodal walls in PtGa - J.-Z. Ma (Nature Portfolio, 2021)
In all experimentally observed Weyl semimetals so far, the Weyl points always appear in pairs in the momentum space. Here, the authors report one unpaired Weyl point without surface Fermi arc emerging at the center of the Brillouin zone, which is surrounded by charged Weyl nodal walls in PtGa.